Pay and employee intrapreneurialism in Russia, 1994–2015: A longitudinal study - Richard Croucher; Claudio Morrison; Marian Rizov (European Management Review, 2023)
We examine whether a high wage–high employee intrapreneurial inputs model remains a significant feature of the Russian economy. We do so by estimating the evolution of employee `intrapreneurial' contributions to companies in Russia, 1994–2015, using Akerlof's theory of `partial gift exchange'. Akerlof (1982) suggests that employee discretionary contributions to organizational capacities rise when pay exceeds employee perceptions of `fair' pay in comparable employment. Using the extensive Russian Longitudinal Monitoring Survey (RLMS), we find that overall employee intrapreneurial contributions significantly declined, 1994– 2015, mirroring the declining Akerlof wage premium. Intrapreneurialism in highly informalized sectors was associated with labour market pressures. We extend Akerlof's theory to recognize intrapreneurial activity associated with coercive labour market pressures in the secondary labour market.
Keywords: 650; implicit gift exchange; intrapreneurship; market pressure; remuneration systems; Russia; wage premium